Implementasi Sistem Pengukuran Suhu Pada Pemindahan Pola Gambar Ke Papan Tembaga Dalam Pembuatan PCB - Nur Alam; Taufik Hidayat (Institut Sains dan Teknologi Nasional, 2021)
This research has succeeded in implementing a PLC-Based Temperature Control System for Transferring Image Patterns to Copper Boards in PCB (Printed Circuit Board) Manufacturing. This tool is made to simplify and speed up the process of transferring image patterns to copper boards in PCB manufacture. This Regulatory System consists of HMI, PLC, Thermocouple, Transmitter Thermocouple, Heater, as well as iron coating mechanics. HMI serves to display the settings received by the PLC as well as a second controller. While the PLC functions as a data processing center needed by the system and the main controller, the thermocouple functions to issue an output in the form of voltage. Heater as a heater and Mechanics of iron layer as pressure on the copper board. The results of the research on this system are image patterns that can be transferred to the copper board automatically with a measured temperature range of 400C - 1000C.